Leucobacter soli sp. nov., from soil amended with humic acid. Issue 12 (14th December 2021) - Kämpfer, Peter; McInroy, John A.; Clermont, Dominique; Neumann-Schaal, Meina; Criscuolo, Alexis; Busse, Hans-Jürgen; Glaeser, Stefanie P.
Abstract : A Gram-positive, non-spore-forming actinobacterium (IMT-300 T ) was isolated from soil amended with humic acid in Malvern, AL, USA. This soil has been used for 50+years for the cultivation of earthworms for use as fish bait. Based on 16S rRNA gene sequence similarity studies, strain IMT-300 T was shown to belong to the genus Leucobacter and was closely related to the type strain of 'Leucobacter margaritiformis ' L1 T (97.8%). Similarity to all other type strains of Leucobacter species was lower than 97.2 %. The average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values between the IMT-300 T genome assembly and those of the closest relative Leucobacter type strain were 81.4 and 23.3 % ( Leucobacter chironomi ), respectively. The peptidoglycan of strain IMT-300 T contained l -2, 4-diaminobutyric acid as the diagnostic diamino acid. In addition, glycine, d - and l -alanine and d -glutamic acid were found. The peptidoglycan type represents a variant of B2δ (B11). The major quinones were menaquinones MK-10 and MK-11. The polar lipid profile consisted of the major lipids diphosphatidylglycerol, phosphatidylglycerol and moderate to minor amounts of two unidentified phospholipids, two unidentified glycolipids and an unidentified aminophospholipid. The polyamine pattern contained major amounts of spermidine and spermine. Strain IMT-300 T contained the major fatty acids C15 : 0 anteiso, C16 : 0 iso and C17 : 0 anteiso, like other members of the genus Leucobacter . The results of ANI and dDDH analyses and physiological and biochemical tests allowed a genotypic and phenotypic differentiation of strain IMT-300 T from the most closely related Leucobacter species. Strain IMT-300 T represents a novel Leucobacter species, for which we propose the name Leucobacter soli sp. nov., with the type strain IMT-300 T (CIP 111803 T =DSM 110505 T =CCM 9020 T =LMG 31600 T ).